2014
DOI: 10.1021/ie502799f
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Reactivity and Receptivity of Alloy and Tool Steels for Phosphate Conversion Coatings: Role of Surface Mechanical Attrition Treatment

Abstract: The role of surface mechanical attrition treatment (SMAT) in the phosphatability of EN8, EN19, and H11 steels using a zinc phosphating bath and the corrosion resistance of the resultant coatings are addressed. SMAT generated a uniform surface profile, increased the surface roughness, and decreased the grain size, which helped to increase the extent of metal dissolution during phosphating and the rate of growth of zinc phosphate coating. In spite of the similarity in phase composition, the phosphate crystal siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The ability to generate functionally gradient materials, with a nanocrystalline surface layer that provides the desirable surface properties and the matrix with a coarse-grained structure that offers the ductility, is a promising attribute of SMAT. Using this method, it is possible to produce thicker nanocrystalline and work-hardened surface layers, as well as deeper surface regions with larger residual compressive stresses. , The surface nanocrystallization and refinement of grain size after SMAT helps to increase the kinetics of diffusion of boron during pack boronizing and plasma nitriding of 304 grade stainless steel (304 SS). , In addition, they also accelerate the deposition of phosphate conversion coatings on EN8-grade medium carbon steel, EN19-grade alloy steel, and H11-grade tool steel …”
Section: Introductionmentioning
confidence: 99%
“…The ability to generate functionally gradient materials, with a nanocrystalline surface layer that provides the desirable surface properties and the matrix with a coarse-grained structure that offers the ductility, is a promising attribute of SMAT. Using this method, it is possible to produce thicker nanocrystalline and work-hardened surface layers, as well as deeper surface regions with larger residual compressive stresses. , The surface nanocrystallization and refinement of grain size after SMAT helps to increase the kinetics of diffusion of boron during pack boronizing and plasma nitriding of 304 grade stainless steel (304 SS). , In addition, they also accelerate the deposition of phosphate conversion coatings on EN8-grade medium carbon steel, EN19-grade alloy steel, and H11-grade tool steel …”
Section: Introductionmentioning
confidence: 99%
“…Surface roughening by mechanical method such as sandpaper abrading increased the metal dissolution and hence the nucleation rate at the beginning of phosphating was also accelerated and thus a coating with fine granules could be obtained. This rule is the same for other kind of metals such as steel and non‐ferrous metals . However, the difference lays in the ease of corroding different substrates and this is the reason why granules on Ti are sparse and large whereas those on easily corroded metals are dense and showed fine flake or flower‐like shapes.…”
Section: Resultsmentioning
confidence: 85%
“…In this study, although the EDS analysis revealed the coexistence of O, Ti, P, and Zn in the coating, the XRD patterns excluded presence of Hopeite. Surface roughness determined the number and size of granule, whereas it was the acidity of convention solution that determined the phase composition of the PCC . If the pH is low, the volume fraction of Hopeite in the coating will be obviously decreased.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations